The Managed Body Developing Girls and Menstrual Health in the Global South - Bobel, Chris (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
The Managed Body is an invested critique of the discourses of 'Menstrual Hygiene Management' (MHM)--a growing social movement to support menstruating girls in low and middle income countries. Bobel shows how MHM organizations frame the issues by claiming menstruating girls encounter 'a hygienic crisis' that authorizes rescue. Faced by the challenges of capturing attention and directing resources, MHM advocates often inadvertently rely upon weak evidence and spectacularized representations to promote a product-centered, consumerist agenda that actually accommodates more than it resists the core problem of menstrual stigma.